Prevalence of extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae in wastewater: a systematic review and meta-analysis - Nawel Zaatout; Samia Bouras; Nouria Slimani (IWA Publishing, 2021)
Wastewater is considered a hotspot niche of multi-drug and pathogenic bacteria such as Enterobacteriaceae-producing extended-spectrum beta-lactamases (ESBL-E). Thus, the aim of this meta-analysis was to evaluate the prevalence of ESBL-E in different wastewater sources. Different databases (Medline, EMBASE, and Cochrane Library) were searched from inception to March 2021. Data were analyzed using random-effects modeling, and subgroup and meta-regression analyses were used to ascertain heterogeneity among the subgroups. Fifty-seven observational studies were selected, and the pooled prevalence of ESBL-E in wastewater was 24.81% (95% CI, 19.28-30.77). Escherichia coli had the highest ESBL prevalence. The blaCTX-M genes were the most prevalent in the selected studies (66.56%). The pooled prevalence of ESBL was significantly higher in reports from America (39.91%, 95% CI, 21.82-59.51) and reports studying hospital and untreated wastewaters (33.98%, 95% CI, 23.82-44.91 and 27.36%, 95% CI, 19.12-36.42). Overall, this meta-analysis showed that the prevalence of ESBL-E in wastewater is increasing over time and that hospital wastewater is the most important repository of ESBL-E. Therefore, there is a need for developing new sewage treatment systems that decrease the introduction of resistant bacteria and antibiotic residues. HIGHLIGHTS The global prevalence of Enterobacteriaceae-producing extended-spectrum beta-lactamases (ESBL-E) in wastewater was found to be 24.81%.; The pooled prevalence of ESBL-E was significantly higher in reports studying hospital wastewater.; The highest prevalence of ESBL-E was in America, and the lowest prevalence was in Europe.; Among ESBL genes, blaCTX-M genes had the highest prevalence, followed by blaTEM and blaSHV.;